Bidirectional converter design for battery charging system in DC microgrid - Chan, Nyein Soe (2016)
Efficient energy storage system is one of the most vital elements in a DC micro gird. The efficient of the energy storage system mainly depends on the converter that is used. Therefore, it is very important to achieve the high efficiency during power conversion process. This project focuses on the design of a bidirectional DC-DC converter for a battery charging system which will be used in DC micro gird. The interleaving topology is explored and discussed in this project to improve efficiency, reduce ripple and shrink the size of capacitors and inductors in DC-DC converter. The closed loop control of multiphase interleaved DC-DC converter is implemented in the MATLAB Simulink software. The average current control loop system will be discussed to observe the simulation results. Moreover, the phase shedding technique will also be introduced to improve the efficiency of the DC-DC converter while operating at light load situation.